SSI influence on the seismic response of asymmetrical small, low-rise R/C buildings. (August 2021) - Askouni, Paraskevi K.; Karabalis, Dimitris L.
Highlights: Elastoplastic behavior of reinforced concrete elements according to a fiber model. Asymmetry of the relative stiffness of vertical reinforced concrete elements. The Soil-Structure Interaction effect on asymmetrical R/C 3-D buildings. Comparison of foundation mat and footings to the assumption of a rigid base. Non-linear time-history earthquake analysis under 3-D accelerograms. Abstract: In the current work, a series of seismic analyses of asymmetrical small, low-rise 3-D reinforced concrete (R/C) buildings is executed along with the investigation of the effect of deformable soil on the seismic structural response. The time-history analyses are performed by using earthquake accelerograms in two horizontal and one vertical direction, while the elastoplastic behavior of R/C elements is regarded with a fiber mechanical analytical model. The foundation of the buildings is designed in two ways, either as R/C footings interconnected with R/C beams or as foundation mat. The Soil-Structure Interaction (SSI) effect on the seismic response is studied not only through the global structural characteristics but also through detailed parameters, such as the redistribution of the internal forces of R/C elements. The simple maximum softening damage index is employed to evaluate the elastoplastic behavior of R/C structures.